A new reasonable scenario to search for ER-alpha energy-time-position correlated sequences in a real time mode - Tsyganov, Yu. S. (Physics of particles and nuclei letters, 2015)
A new real-time PC based algorithm and a compact C ++ code to operate in a real-time mode with a 48 × 128 strip double side position sensitive large area silicon radiation detector Micron Semiconductors (UK) are developed and tested. Namely with this new approach it has become possible to provide the quick extraction of EVR-alpha correlated sequences in heavy ion induced complete fusion nuclear reactions. Specific attention is paid to the application of new CAMAC 4 M modules for charge particle position measurement during long-term experiments aimed to the synthesis of new superheavy nuclei. Some attention is paid to the different (combined) algorithm scenario to search for ER-alpha and alpha-alpha chains.